Dogs, but Not Wolves, Lose Their Sensitivity Toward Novelty With Age - Hansen Wheat, Christina; van der Bijl, Wouter; Temrin, Hans (Frontiers in Psychology, 2019)
Selection on behavioural traits holds a prominent role in the domestication of animals, and domesticated species are generally assumed to express reduced fear and reactivity towards novel stimuli compared to their ancestral species. However, very few studies have explicitly tested this proposed link between domestication and reduced fear responses. Of the limited number of studies experimentally addressing the alterations of fear during domestication, the majority has been done on canids. These studies on foxes, wolves and dogs suggest that decreased expression of fear in domesticated animals is linked to a domestication-driven delay in the first onset of fearful behaviour during early ontogeny. Thus, wolves are expected to express exaggerated fearfulness earlier during ontogeny compared to dogs. However, while adult dogs are less fearful towards novelty than adult wolves and wolf-dog hybrids, consensus is lacking on when differences in fear expression arise in wolves and dogs. Here we present the first extended examination of fear development in hand-raised dogs and European grey wolves, using repeated novel object tests from six to 26 weeks of age. Contrary to expectations, we found no evidence in support of an increase in fearfulness in wolves with age or a delayed onset of fear response in dogs compared to wolves. Instead, we found that dogs strongly reduced their fear response in the period between six and 26 weeks of age, resulting in a significant species difference in fear expression towards novelty from the age of 18 weeks. Critically, as wolves did not differ in their fear response towards novelty over time, the detected species difference was caused solely by a progressive reduced fear response in dogs. Our results thereby suggest that species differences in fear of novelty between wolves and dogs are not caused by a domestication-driven shift in the first onset of fear response. Instead, we suggest that a loss of sensitivity towards novelty with age in dogs causes the difference in fear expression towards novelty in wolves and dogs.